A framework of scenario-epistemic game for proffesional skills and higher order thinking skills - Kho, Pui Wun (2014)
In the era of globalisation, there is a competition for innovative work. The world is racing ahead to produce innovative and creative workers who have professional skills to solve the complex problems (Friedman, 2005). Dede (2007) also agreed that the world will be dominated by innovation and knowledge. Employers have higher expectation on their workers. They are required to reason, analyse, evaluate and communicate effectively (Siti Noridah, 2012). Wagner (2008) designated that these are the vital survival skills that must be possessed by every individual. This has driven the workers towards higher challenges as they need to equip themselves with 21st century skills to deal with 21st century tasks (Partnership for 21st Century Skills, 2008).